The design of metabolic cage for the non-human primates. - Vellayan , S.; Hutagalung, R. I. (1980)
A study was undertaken to develop a suitable metabolic cage for the non-human primates, siamangs and lar gibbons (Symphalangus and Hylobates sp.) The newly design cage is found practical and applicable for undertaking balance trial and digestibility studies with both solid and semi-solid diets.